Immobilization of 2‐Deoxy‐d–ribose‐5‐phosphate Aldolase on Membrane Supports by Spray‐Coating: Optimization by Design‐of‐Experiment. Issue 21 (5th October 2022) - Fischer, Thilo; Sperling, Marcel; Rosencrantz, Sophia; Wäscher, Martin; Pietruszka, Jörg; Reinicke, Stefan
Abstract: A strategy for the immobilization of the enzyme 2‐deoxy‐d ‐ribose‐5‐phosphate aldolase (DERA) is presented via spray‐coating on membrane support material to generate an enzymatically active membrane which can be used in continuously run synthesis modules. A functional, water‐soluble copolymer containing addressable units to covalently bind DERA is mixed with the enzyme, followed by spray‐coating of the mixture onto polyacrylonitrile/polyethylene imine‐ (PAN/PEI) membranes and a subsequent post‐processing to stabilize the coating. Confirmation of successful immobilization was achieved by atomic force microscopy (AFM) imaging and assessment of retained enzyme activity. Through variation of relevant parameters, improvements in stability and activity were seen, which formed the basis for the following optimization by Design‐of‐Experiment (DoE). A first fractional factorial design yielded additional performance improvements and important insights into the impacts of experimental parameters and their interaction. A second full factorial design did not result in further improvements, but validated the results of the first design. Abstract : Immobilization on a membrane : Deoxy‐d ‐ribose‐5‐phosphate aldolase (DERA) is immobilized within a thin polymer film on a membrane support via a spray‐coating approach. Such membranes can be used in continuous flow reactors for the synthesis of enantiomerically pure β ‐hydroxyaldehydes. In this contribution, the immobilization protocol is established and optimized using a design‐of‐experiment approach.